2019
DOI: 10.1002/ente.201900405
|View full text |Cite
|
Sign up to set email alerts
|

A New Finding on the Enhancement of the Ability of Polysulfide Adsorption of V2O5 by Doping Tungsten in Lithium–Sulfur Batteries

Abstract: Lithium–sulfur batteries are considered to be the most commercially promising lithium metal secondary batteries due to their high specific capacity. However, the shuttle effect of lithium polysulfide (LiPS) in the electrolyte seriously hinders the development of lithium–sulfur batteries. W‐doped V2O5 (W‐V2O5) is prepared by a hydrothermal method, which greatly improves the LiPS adsorption ability of V2O5. The W‐V2O5 powder can discolor the LiPS solution in 1 min. Then, W‐V2O5 is combined with a graphene/carbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Comparatively, the battery with CNT/ZnS/S 85% showed a relative high R s of 1.39 ohm, while R s values for other batteries were so small (<1 ohm) that could be ignored. The negligible R s and sharp-decreased R ct indicated high charge transfer at surface/interface and in the bulk, which is related to the redistribution of sulfur on the surface of the S/CNT frame and some active substances dissolved in the electrolytes [61]. With the discharge/charge cycling, on one hand, sulfur was redoxidized and redistributed on the electrode surface, thus the sulfur aggregation was prevented and the electrical contact was improved which led to rapidly decreased R s ; on the other hand, the electron transport pathways were gradually stabilized in this process, resulting in the significant decrease of R ct .…”
Section: Resultsmentioning
confidence: 99%
“…Comparatively, the battery with CNT/ZnS/S 85% showed a relative high R s of 1.39 ohm, while R s values for other batteries were so small (<1 ohm) that could be ignored. The negligible R s and sharp-decreased R ct indicated high charge transfer at surface/interface and in the bulk, which is related to the redistribution of sulfur on the surface of the S/CNT frame and some active substances dissolved in the electrolytes [61]. With the discharge/charge cycling, on one hand, sulfur was redoxidized and redistributed on the electrode surface, thus the sulfur aggregation was prevented and the electrical contact was improved which led to rapidly decreased R s ; on the other hand, the electron transport pathways were gradually stabilized in this process, resulting in the significant decrease of R ct .…”
Section: Resultsmentioning
confidence: 99%
“…The adsorption XPS spectroscopy revealed a decrease in the binding energies of Co 2+ and Mo 6+ by 0.77 and 0.13 eV, respectively. Furthermore, in situ XRD analyses demonstrated that the diffraction peak of S8 gradually weakened with the discharge reaction, and S 8 began to be converted to LiPSs and finally to Li 2 S. Gao et al 37 employed a hydrothermal method to prepare tungsten−doped V 2 O 5 (W−V 2 O 5 ), which was then combined with graphene/carbon nanotube composites (G/ CNTs) and coated onto PP separators. The inclusion of tungsten enhances the adsorption capacity of V 2 O 5 , and V 5+ ions facilitate the oxidation of LiPS, resulting in the generation of sulfur oxides and the formation of Li−V−O−S complexes.…”
Section: ■ Inorganic-based Modificationsmentioning
confidence: 99%
“…[ 21 ] However, the interaction between nonpolar carbon and polar polysulfides is not sufficient to effectively immobilize polysulfides in the cathode side. [ 22 ] To strengthen the adsorption capacity of polysulfides, polar materials such as metal oxides (CeO 2 [ 23 ] and V 2 O 5 [ 24 ] ) and metal sulfides (ZnS [ 25 ] and MoS 2 [ 26 ] ) have been used to modify the separators. [ 27 ] Beyond that, some multielement metal oxides containing two metal ions and oxygen anions, such as CoMoO 4 , MnFe 2 O 4 , and LiV 3 O 8 , have stronger interactions with polysulfides.…”
Section: Introductionmentioning
confidence: 99%